Answer:
Choice A is correct. (-1,3) is the solution.
Explanation:
We have given the system of linear equations:
2x+y=1 (eq I)
3x-y=-6 (eq Ii)
We have to find the solution of system of linear equations.
find the value of y from (eq I) and put in (eq II) we have,
y = 1 - 2x ( eq III)
Now put this value is (eqI) .
3x-(1 - 2x) = -6
3x - 1 + 2x = -6
5x = -6+1
5x = -5
x = -1
Now, put this value of x in ( eq III) we have,
y = 1 - 2(-1)
y = 1 +2
y = 3
(-1,3) is the solution to this system of linear equations.